2023
DOI: 10.3390/ph16020151
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery and Development Targeting Dementia

Abstract: Dementia, most often associated with neurodegenerative diseases, affects millions of people worldwide, predominantly the elderly. Unfortunately, no treatment is still available. Therefore, there is an urgent need to address this situation. This review presents the state of the art of drug discovery and developments in targeting dementia. Several approaches are discussed, such as drug repurposing, the use of small molecules, and phosphodiesterase inhibitors. Furthermore, the review also provides insights into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…These experiments showed that the progress of neuronal destruction processes slowed down [ 201 ]. Moreover, the activity of the β-secretase enzyme, which is mainly responsible for the formation of β-amyloid deposits, was reduced, which is a key and important achievement in the therapy of patients suffering from Alzheimer’s disease [ 202 ]. Scientists are also trying to determine the clinical usefulness of TNF-α synthesis inhibitors, which include, inter alia, imide immunomodulatory drugs, including thalidomide [ 6 ].…”
Section: Treatment Of Inflammation In Admentioning
confidence: 99%
“…These experiments showed that the progress of neuronal destruction processes slowed down [ 201 ]. Moreover, the activity of the β-secretase enzyme, which is mainly responsible for the formation of β-amyloid deposits, was reduced, which is a key and important achievement in the therapy of patients suffering from Alzheimer’s disease [ 202 ]. Scientists are also trying to determine the clinical usefulness of TNF-α synthesis inhibitors, which include, inter alia, imide immunomodulatory drugs, including thalidomide [ 6 ].…”
Section: Treatment Of Inflammation In Admentioning
confidence: 99%
“…96 It is now under another clinical trial study designed to further evaluate its effect on AD improvement. 97…”
Section: Discussionmentioning
confidence: 99%
“…Therapies for AD are usually designed to promote the removal or destruction of amyloid proteins (Aβ protein in the case of AD) or their cleavage products, based on the hypothesis that the observed amyloid causes disease (amyloid cascade hypothesis [ 6 , 7 , 8 ]). However, these therapies have failed to significantly reverse the course of AD [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introduction: Previous Data and Our Best-fit Modelmentioning
confidence: 99%